Resituating relaunched migration systems as emergent entities manifested in geographic structures. (20th December 2017) - DeWaard, Jack; Ha, Jasmine Trang
Abstract: While important and timely, the recent effort to 'relaunch' migration systems as emergent entities is premised on a mischaracterization and subsequent dismissal of decades of research showing that systems are ultimately expressed in geographic structures in the form of migration networks comprised of a set of places that are connected to one another by migration flows. In this paper, we reconcile this relaunch with past research on migration systems by considering whether and how changes in some of the actors and dynamics that create and sustain migration systems are expressed in corresponding changes in the geographic structure of migration flows. By elucidating these linkages, our work helps to strengthen the aforementioned relaunch of migration systems by ensuring greater continuity with prior research and, going forward, the continued utility of a migration systems perspective for diverse audiences and issues.